A high-stability low-chlorine catalyst and its preparation method and application
By preparing low-chlorine catalysts, using imidazole, polyvinyl chloride and strong bases to form active precursors, and combining them with samarium oxy-bromide, phenolic resin and ethyl orthosilicate, the problems of decreasing catalyst activity, poor swelling and high chlorine content are solved, and catalytic effects with high activity, low cost and high stability are achieved.
Patent Information
- Application Number
- CN202210045625.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-15
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-01-15
AI Technical Summary
The existing heterogeneous catalysts have problems such as decreased catalytic activity, poor swelling and clogged reactors in the synthesis of propylene carbonate by CO2 and propylene oxide, and the high chlorine content leads to equipment corrosion.
Using a low chlorine catalyst, catalyst C is obtained by reacting imidazole, polyvinyl chloride and strong alkali in water to form active precursor A, and then mixed with samarium oxy bromide, phenolic resin and ethyl orthosilicate, extruded, dried and calcined. The catalyst has a cylindrical or clover-like shape, with moderate diameter and length, reasonable content of elements such as nitrogen, oxygen, bromine, samarium, Si, and low chlorine content.
It achieves a catalytic effect with high activity and low cost, with high stability of the catalyst and low swelling rate, avoiding reactor clogging, low chlorine content reduces equipment corrosion, and high product selectivity.
Smart Images

Figure 482749DEST_PATH_IMAGE006 
Figure 871639DEST_PATH_IMAGE004
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a solid catalyst for propylene carbonate, in particular to a method for preparing a catalyst for preparing propylene carbonate from CO2 and propylene oxide in a fixed bed reactor. Background Art
[0002] The product propylene carbonate is an organic solvent and organic synthesis intermediate with excellent performance. The cycloaddition of propylene oxide and carbon dioxide to form propylene carbonate is an important way to achieve CO2 emission reduction.
[0003] Heterogeneous catalysts have the characteristics of being easy to separate from the product and regenerate. Therefore, inorganic solid catalysts have become a hot topic of research, and MgO-Al2O3 and SmOCl have relatively good conversion rates and selectivities. However, the solvent DMF is required to provide a catalytic effect. If DMF is not used as a solvent, or other non-polar solvents are used, the conversion rate of the reaction will be very low. The addition of solvents obviously has an adverse effect on the entire process, increases the energy consumption of the reaction, requires product separation, etc., which increases the cost. ZnAl hydrotalcite prepared by coprecipitation and hydrothermal treatment has both abundant alkaline sites and relatively strong acidic sites. Moreover, the anions between the layers have relatively strong nucleophilicity, so it has a certain catalytic activity.
[0004] Alkaline resins with quaternary ammonium salt groups have catalytic activity, but the activity is low, and the reaction can only be fully carried out under high temperature and high pressure.
[0005] Ionic liquids have extremely high catalytic activity. Various functional groups are grafted onto ionic liquids to further improve their catalytic performance. The most important progress is the grafting of alcoholic hydroxyl groups or carboxyl groups onto ionic liquids. As well as grafting ionic liquids onto other carriers containing alcoholic hydroxyl groups or carboxyl groups, such as chitosan and carboxymethyl cellulose. These heterogeneous catalysts have high catalytic activity.
[0006] Patent CN200910237124.0 proposes a solid catalyst, which uses SiO2 prepared by hydrolysis of ethyl orthosilicate as a carrier, zinc salt, halogen and organic amine as active components. The reactants have a high conversion rate.
[0007] Patent CN201210215810.X discloses a catalyst for synthesizing propylene carbonate, which uses a mesoporous silica foam material as a carrier and an ionic liquid as an active component.
[0008] Patent CN201110275209.5 discloses a catalyst for synthesizing propylene carbonate, which uses a polydivinylbenzene polymer as a carrier and an imidazole ionic liquid as an active component. The catalyst was evaluated by the reaction of epoxide and CO2 in a kettle reactor, and the activity of the catalyst was very high.
[0009] Patent CN201210184990.X discloses a catalyst for synthesizing propylene carbonate, which uses a polystyrene polymer as a carrier and a quaternary ammonium salt as an active component.
[0010] Patent CN201310429816.1 discloses a catalyst for synthesizing propylene carbonate, which uses a phenolic resin mesoporous material as a carrier and imidazole as an active component. Imidazole is immobilized on a chloromethylated FDU mesoporous phenolic resin to obtain a chloromethylated FDU mesoporous phenolic resin-loaded imidazolium ion liquid precursor, and then the loaded imidazolium ion liquid precursor is reacted with a halide containing different functional groups to prepare a catalyst.
[0011] However, there are many problems with the currently used heterogeneous catalysts. For example, catalysts grafted with quaternary ammonium salts or ionic liquids usually have the problem of decreased catalytic activity, the polymer carrier has severe swelling, which is not conducive to the loading of the catalyst in the fixed bed reactor, and the reactor may be blocked during the reaction. Summary of the invention
[0012] The technical problem to be solved by the present invention is to provide a high-stability low-chlorine catalyst to facilitate the reaction of synthesizing propylene carbonate from CO2 and propylene oxide on a fixed bed.
[0013] According to a first aspect of the present invention, the present invention provides a low-chlorine catalyst for preparing propylene carbonate.
[0014] The low-chlorine catalyst for preparing propylene carbonate of the present invention has the following chemical composition by mass: nitrogen content of 3.6-10.9%, oxygen content of 12.1-14.4%, bromine content of 6.1-9.0%, chlorine content of 0.1-0.4%, samarium content of 12.2-17.2%, Si content of 2.3-2.7%, and the remainder of carbon and hydrogen.
[0015] Furthermore, the catalyst is cylindrical or clover-shaped, the catalyst diameter is generally 0.1-0.3 cm, and the length is generally 1-3 cm.
[0016] According to the second aspect of the present invention, the present invention also provides a method for preparing the above catalyst.
[0017] The preparation method of the low-chlorine catalyst provided by the present invention comprises the following steps:
[0018] (1) Put imidazole, polyvinyl chloride and alkali into water, stir and dissolve, then heat to 60-90°C for 1-5 hours; after cooling, filter to obtain a gray-black solid, and dry to obtain an active precursor A;
[0019] (2) The active component A is mixed evenly with samarium oxybromide, phenolic resin and tetraethyl orthosilicate, extruded into strips, and then dried and calcined to obtain catalyst C.
[0020] Furthermore, the average degree of polymerization of the polyvinyl chloride in step (1) is 1000-3000, and the chlorine content is 40%-60%. The alkali is at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, potassium carbonate, etc., preferably sodium hydroxide. The mass ratio of imidazole to polyvinyl chloride, alkali, and water is 1: (1-4): (2-12): (8-20), preferably 1: (2-3): (6-10): (14-18).
[0021] Furthermore, the drying conditions in step (1) are as follows: the drying temperature is 80-100° C. and the drying time is 10-24 hours.
[0022] Furthermore, the phenolic resin described in step (2) is a thermosetting phenolic resin, with a solid content of ≥50% and a free phenol content of ≤10%. In step (2), the weight ratio of active component A to samarium oxybromide, phenolic resin, and tetraethyl orthosilicate is 1: (0.5-1.5): (0.5-2): (0.5-1), preferably 1: (0.8-1.3): (1.0-1.5): (0.6-0.8).
[0023] Furthermore, the molding in step (2) can be cylindrical, clover-shaped, etc., preferably clover-shaped. The drying conditions in step (2) are: drying temperature of 110-130°C, drying time of 10-24 hours; roasting temperature of 150-180°C, roasting time of 0.5-4 hours.
[0024] According to the third aspect of the present invention, the present invention also provides a method for synthesizing propylene carbonate, wherein the catalyst described above is used.
[0025] Furthermore, the conditions for the catalytic reaction of CO2 and propylene oxide are as follows: the molar ratio of CO2 to propylene oxide is 2:1~1.5:1, and the volume space velocity (LHSV) is 1~3h -1 , the reaction pressure is 2~4MPa, and the reaction temperature is 90~160℃.
[0026] Compared with the existing catalysts, the present invention has the following beneficial effects:
[0027] 1. The catalyst of the present invention has the characteristics of high activity and low cost. The main catalyst of the catalyst is a quaternary ammonium salt generated by polyvinyl chloride and imidazole, and samarium oxybromide. The presence of a strong base removes the chloride ion exchange and improves the basicity of the co-catalyst. At the same time, the strong base catalyzes tetraethyl orthosilicate to generate active silicon oxide, and the active silicon oxide provides hydrogen bonds with the phenolic resin, and activates CO2 and propylene oxide respectively with the strong Lewis acid and base of the co-catalyst to form a synergistic catalytic effect. At the same time, the quaternary ammonium salt generated by polyvinyl chloride has a larger unit density and more catalytic active centers. The catalyst has high catalytic activity. The raw material cost of the catalyst of the present invention is low, and the preparation process is simple and the production cost is low.
[0028] 2. The catalyst of the present invention has a low chlorine content, has little corrosion to equipment, and has good quality of propylene carbonate products. In the preparation process of the catalyst of the present invention, a strong base is used to exchange chlorine ions and remove part of the chlorine ions, so the chlorine content in the catalyst is low.
[0029] 3. Ordinary resin catalysts usually need to be swollen and mixed with inorganic inert materials to avoid clogging of the fixed bed reactor due to swelling of the catalyst during the reaction. The catalyst of the present invention has an extremely low swelling rate and does not need to be swollen during use. The catalyst can be directly loaded into the fixed bed reactor. DETAILED DESCRIPTION
[0030] The technical scheme of the present invention is further described below in conjunction with specific embodiments. The polyvinyl chloride used in the embodiments is commercially available, has an average molecular weight of 1500, and a chlorine content of 51%. The benzaldehyde resin used is a commercially available resin, and has a free phenol content of 9%. The element detection of the catalyst adopts a ZSX100e X-ray fluorescence spectrometer produced by Rigaku Corporation of Japan.
[0031] The experiment uses the area normalization method to determine the content of each component in the sample, so as to calculate the conversion rate and selectivity. The calculation formula is as follows:
[0032]
[0033]
[0034] .
[0035] Example 1
[0036] (1) 20 g of imidazole, 20 g of polyvinyl chloride, and 40 g of sodium hydroxide were placed in 160 g of water, stirred to dissolve, and then heated to 60°C for 1 hour. After cooling, a gray-black solid was obtained by filtration, and dried at 80°C for 10 hours to obtain an active precursor A1.
[0037] (2) 30 g of active component A1 was mixed evenly with 15 g of samarium oxybromide, 15 g of phenolic resin and 15 g of tetraethyl orthosilicate, extruded into strips, dried at 110-130°C for 10-24 hours, and then heated at 150-180°C for 0.5-4 hours to obtain catalyst C1. The composition of catalyst C1 is listed in Table 1.
[0038] Example 2
[0039] (1) 20 g of imidazole, 80 g of polyvinyl chloride, and 240 g of sodium hydroxide were placed in 800 g of water, stirred to dissolve, and then heated to 100°C for 5 hours. After cooling, the gray-black solid was filtered and dried at 90°C for 24 hours to obtain the active precursor A2.
[0040] (2) 40 g of active component A2 was mixed evenly with 60 g of samarium oxybromide, 80 g of phenolic resin and 40 g of tetraethyl orthosilicate, extruded into strips, dried at 130°C for 24 hours and then heated at 180°C for 4 hours to obtain catalyst C2. The composition of catalyst C2 is listed in Table 1.
[0041] Example 3
[0042] (1) 20 g of imidazole, 40 g of polyvinyl chloride, and 120 g of sodium hydroxide were placed in 280 g of water, stirred to dissolve, and then heated to 80°C for 2 hours. After cooling, the gray-black solid was filtered and dried at 80°C for 12 hours to obtain the active precursor A3.
[0043] (2) 30 g of active component A3 was mixed evenly with 24 g of samarium oxybromide, 30 g of phenolic resin and 18 g of tetraethyl orthosilicate, extruded into strips, dried at 110-130°C for 10-24 hours, and then heated at 150-180°C for 0.5-4 hours to obtain catalyst C3. The composition of catalyst C3 is listed in Table 1.
[0044] Example 4
[0045] (1) 20 g of imidazole, 60 g of polyvinyl chloride, and 200 g of sodium hydroxide were placed in 360 g of water, stirred to dissolve, and then heated to 80°C for 4 hours. After cooling, the gray-black solid was filtered and dried at 90°C for 20 hours to obtain the active precursor A4.
[0046] (2) 40 g of active component A4 was mixed evenly with 52 g of samarium oxybromide, 60 g of phenolic resin and 32 g of tetraethyl orthosilicate, extruded into strips, dried at 120°C for 15 hours and then heated at 170°C for 2 hours to obtain catalyst C4. The composition of catalyst C4 is listed in Table 1.
[0047] Example 5
[0048] (1) 20 g of imidazole, 50 g of polyvinyl chloride, and 160 g of sodium hydroxide were placed in 320 g of water, stirred to dissolve, and then heated to 90°C for 4 hours. After cooling, the gray-black solid was filtered and dried at 100°C for 24 hours to obtain the active precursor A5.
[0049] (2) 40 g of active component A5 was mixed evenly with 40 g of samarium oxybromide, 48 g of phenolic resin and 28 g of tetraethyl orthosilicate, extruded into strips, dried at 130°C for 24 hours and then heated at 150°C for 1 hour to obtain catalyst C5. The composition of catalyst C5 is listed in Table 1.
[0050] Example 6
[0051] (1) 20 g of imidazole, 50 g of polyvinyl chloride, and 160 g of potassium hydroxide were placed in 320 g of water, stirred to dissolve, and then heated to 90°C for 4 hours. After cooling, the gray-black solid was filtered and dried at 100°C for 24 hours to obtain the active precursor A6.
[0052] (2) 40 g of active component A6 was mixed evenly with 40 g of samarium oxybromide, 48 g of phenolic resin and 28 g of tetraethyl orthosilicate, extruded into strips, dried at 130°C for 24 hours, and then heated at 150°C for 1 hour to obtain catalyst C6. The composition of catalyst C6 is listed in Table 1.
[0053] Example 7
[0054] (1) 20 g of imidazole, 50 g of polyvinyl chloride, and 160 g of sodium carbonate were placed in 320 g of water, stirred to dissolve, and then heated to 90°C for 4 hours. After cooling, the gray-black solid was filtered and dried at 100°C for 24 hours to obtain the active precursor A7.
[0055] (2) 40 g of active component A7 was mixed evenly with 40 g of samarium oxybromide, 48 g of phenolic resin and 28 g of tetraethyl orthosilicate, extruded into strips, dried at 130°C for 24 hours and then heated at 150°C for 1 hour to obtain catalyst C7. The composition of catalyst C7 is listed in Table 1.
[0056] Comparative Example 1
[0057] (1) 20 g of chlorine balls, 8 g of 1-methylimidazole and 80 g of toluene were added to a three-necked flask and refluxed at 110°C for 24 hours; after filtering, the mixture was washed three times with toluene and ethanol, and then vacuum dried at 80°C for 24 hours to obtain the active component Ap.
[0058] (2) 20 g of the active component Ap, 20 g of samarium chloride, 20 g of phenolic resin and 2 g of urotropine were pulverized and mixed to prepare a powder; the powder was pressed into tablets and then heated at 180°C for 2 hours under nitrogen protection to obtain a catalyst Cp. The composition of the catalyst Cp is listed in Table 1.
[0059] The elemental compositions of the catalysts prepared in Examples 1-7 and Comparative Example 1 are shown in Table 1.
[0060] Table 1 Catalyst element composition (unit: wt%)
[0061]
[0062] Example 8
[0063] The catalyst of Example 1 was loaded into a fixed bed microreactor and its activity was evaluated. 200 mL of the catalyst was loaded into a reaction tube with a diameter of 5 cm and a length of 60 cm, and the air tightness was checked. The temperature was then quickly raised to 90°C, and then slowly raised to the reaction temperature to avoid a violent reaction and causing a temperature runaway. After the reaction temperature was kept constant for 1 hour, sampling began. The evaluation results are shown in Table 2. The reaction conditions were as follows: the molar ratio of CO2 to propylene oxide was 2:1, and the volume space velocity was 1 h -1 , reaction temperature is 120℃, reaction pressure is 2MPa. The reaction results are listed in Table 2.
[0064] Example 9
[0065] The catalyst of Example 2 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0066] Example 10
[0067] The catalyst of Example 3 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0068] Embodiment 11
[0069] The catalyst of Example 4 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0070] Example 12
[0071] The catalyst of Example 5 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0072] Example 13
[0073] The catalyst of Example 6 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0074] Embodiment 14
[0075] The catalyst of Example 7 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0076] Comparative Example 2
[0077] The catalyst of Comparative Example 1 was loaded into a reactor, and the reaction conditions were the same as those of Example 8. The reaction results are listed in Table 2.
[0078] The reaction results in Table 2 show that the catalyst of the present invention is a highly active catalyst with high stability. The conversion rate of the reactants is only slightly reduced after 300 hours under the reaction conditions, and the selectivity of the product reaches more than 99%.
[0079] Table 2 Catalyst evaluation results (unit, mol%)
[0080]
Claims
1. A low-chlorine catalyst for preparing propylene carbonate, characterized in that: The chemical composition by mass is as follows: nitrogen content is 3.6 to 10.9%, oxygen content is 12.1 to 4.4%, bromine content is 6.1 to 9.0%, chlorine content is 0.1 to 0.4%, samarium content is 12.2 to 17.2%, Si content is 2.3 to 2.7%, and the balance is carbon and hydrogen; The preparation method of the low-chlorine catalyst comprises the following steps: (1) Put imidazole, polyvinyl chloride and alkali into water, stir and dissolve, then heat to 60-90°C for 1-5 hours; after cooling, filter to obtain gray-black solid, and dry to obtain active precursor A; (2) The active component A is mixed evenly with samarium oxybromide, phenolic resin and tetraethyl orthosilicate, extruded into strips, and dried and calcined to obtain catalyst C; The average degree of polymerization of the polyvinyl chloride is 1000-3000, and the chlorine content is 40%-60%. The calcination temperature in step (2) is 150-180°C.
2. The low-chlorine catalyst according to claim 1, characterized in that The catalyst is in the shape of a clover leaf, with a diameter of 0.1-0.3 cm and a length of 1-3 cm.
3. The low-chlorine catalyst according to claim 1, characterized in that The alkali is sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate or potassium carbonate.
4. The low-chlorine catalyst according to claim 3, characterized in that The alkali is sodium hydroxide.
5. The low-chlorine catalyst according to claim 1, characterized in that The mass ratio of imidazole to polyvinyl chloride, alkali and water is 1: (1~4): (2~12): (8~20).
6. The low-chlorine catalyst according to claim 5, characterized in that The mass ratio of imidazole to polyvinyl chloride, alkali and water is 1:(2~3):(6~10):(14~18).
7. The low-chlorine catalyst according to claim 1, characterized in that The phenolic resin described in step (2) is a thermosetting phenolic resin with a solid content of ≥50% and a free phenol content of ≤10%.
8. The low-chlorine catalyst according to claim 1, characterized in that In step (2), the weight ratio of active component A to samarium oxybromide, phenolic resin and tetraethyl orthosilicate is 1: (0.5-1.5): (0.5-2): (0.5-1).
9. The low-chlorine catalyst according to claim 8, characterized in that In step (2), the weight ratio of active component A to samarium oxybromide, phenolic resin and tetraethyl orthosilicate is 1: (0.8-1.3): (1.0-1.5): (0.6-0.8).
10. The low-chlorine catalyst according to claim 1, characterized in that The drying conditions in step (1) are: drying temperature is 80-100° C., and drying time is 10-24 hours.
11. The low-chlorine catalyst according to claim 1, characterized in that The drying conditions in step (2) are: drying temperature is 110-130° C., drying time is 10-24 hours; and the calcination time is 0.5-4 hours.
12. A method for preparing propylene carbonate by reacting CO2 with propylene oxide, characterized in that: The low-chlorine catalyst described in any one of claims 1 to 11 is used.
13. The method according to claim 12, characterized in that The conditions for the catalytic reaction of CO2 and propylene oxide are as follows: the molar ratio of CO2 to propylene oxide is 2:1~1.5:1, and the volume space velocity (LHSV) is 1~3h -1 , the reaction pressure is 2~4MPa, and the reaction temperature is 90~160℃.
Citation Information
Patent Citations
Catalyst used in synthesis of propylene carbonate and preparation method and application thereof
CN102049303B
Polymer supported imidazole ion catalyst as well as preparation method and application thereof
CN102416348B
Polymer supported quaternary ammonium salt ion catalyst as well as preparation method and application thereof
CN102698799B
Synthetic propylene carbonate catalyst, preparation method and application thereof
CN102728402B
Supported ionic liquid catalyst, as well as preparation and application thereof
CN103495437B